Genomic Characterization of Arcobacter butzleri Isolated From Shellfish: Novel Insight Into Antibiotic Resistance and Virulence Determinants - Fanelli, Francesca; Di Pinto, Angela; Mottola, Anna; Mule, Giuseppina; Chieffi, Daniele; Baruzzi, Federico; Tantillo, Giuseppina; Fusco, Vincenzina (Frontiers in Microbiology, 2019)
Arcobacter butzleri is an emerging pathogenic microorganism, whose taxonomy has been recently suggested to be emended to the Aliiarcobacter butzleri comb. nov.. Despite extensive taxonomic analysis, only few fragmented studies have investigated the occurrence and the prevalence of virulence and antibiotic resistance determinants of this species in strains isolated from shellfish. Herein we report for the first time the whole genome sequencing and genomic characterization of two A. butzleri strains, with particular reference to the antibiotic, heavy metals and virulence determinants. This study supported the taxonomic assignment of these strains to the Aliiarcobacter butzleri species, and allowed us to identify antibiotic and metal resistance along with virulence determinants, also additional to those previously reported for the only two A. butzleri strains from different environments genomically characterized. Beside enlarging the availability of genomic data to perform comparative studies aimed at correlating phenotypic differences associated with ecological niche and geographic distribution with the genetic diversity of A. butzleri spp., this study reports the endowment of antibiotic and heavy metal resistance and virulence determinants of these shellfish-isolated strains. This leads to hypothesize a relatively high virulence of A. butzleri isolated from shellfish and prompt the need for a wider genomic analysis and for in vitro and in vivo studies of more strains isolated from this and other ecological niches, to unravel the mechanism of pathogenicity of this species, and the potential risk associated to their consumption.